Diens van barmhartigheid of diakonaat – hoe belangrik is ’n naam? - William van der Merwe (Verbum et Ecclesia, 2023)
Churches hold different views regarding the office of deacon and role of deacons in the church. Churches also use different terms for their social ministries. This lack of a common language regarding the church’s diaconal ministry often creates confusion in the ecumenical discourse on the diaconate of the church. This article explores the hypothesis that the conceptualisation of a church’s diaconal ministry is influenced by a specific frame of reference, be it a historical perspective, a specific theology or tradition. In this case study of the Dutch Reformed Church (DRC) it is shown how a specific historical and theological understanding of diaconal ministry determines not only this church’s preference for the term ‘service of compassion’ but also its diaconal praxis. The article concludes with a suggestion to the DRC to consider the use of the concept diakonia in contemplation of more active participation in ecumenical disourses regarding the diaconate of the church.